The Effects of Artificial Intelligence as a Tool in French Language Translation Studies in Port Harcourt Metropolis - Jaja, Ethel Kalanne (Cascades, Journal of the Department of French & International Studies, 2025)
The development of artificial intelligence (AI) as a tool in French language translation has had definite impact on translation jobs. People, even professional translators are relying on artificial intelligence in French language translation. Translation studies from the perspective of artificial intelligence (AI) are characterized by intelligence, situational factors and integration. The research fields of translation studies from the perspective of artificial intelligence mainly include the study of translation products quality and effectiveness, the study of translation processes and the study of French language translation teaching. The consequences of all these are that (AI) translation techniques and activities are competing and to an extent replacing human translation. This study explored the effects of artificial intelligence as a tool in the French language translation studies in Port Harcourt metropolis. It evaluated AI and human translation in three areas: logical expression, linguistic style and accuracy of original text. Cognitive theory and the translation theory were explored in the study in the course of which comparative experimental design using the principles of Turing Test was adopted. Linguistic theory, Socio-cultural theory as the practical aspects of these theories were also deployed. The findings revealed that although the emergence of French language translation studies from the perspective of AI promotes a rethinking of theoretical methods in translation research and also advances the transformation of research methods, expanding and deepening the content of French language research, it is observed that artificial intelligence translation has challenges and problems with the choice of content and the logic of the language hence the need for improvement. Besides, artificial intelligence translation now being mechanized is no longer able to analyze the deeper meaning of the author’s message, leading to errors in translations, which errors human translation avoids. It was therefore recommended that improvement on the fidelity of the original language is very paramount. Again, the ministry of education in Nigeria should make the content of artificial intelligence system recognized in tertiary institutions in order to promote the improvement of machine translations so as to meet up with global trend.